FUZZY LIMITS OF FUZZY FUNCTIONS - Altai, Abdulhameed Qahtan Abbood (Malaysian Journal of Science, 2021)
In this paper, we study the theory of fuzzy limit of fuzzy function depending on the Altai’s principle and using the representation theorem (resolution principle) to run the fuzzy arithmetic.